Politics in Farabi’s Reflections - Seyed Mohammad Taqi Chavoshi; Seyed Asef Ehsani (حکمت اسرا, 2013)
In his political plan, Farabi sought to administer his metaphysical project in the human world. Politics is an inseparable part of human life and the only political project that can ensure mankind’s welfare and felicity in his worldly and otherworldly life is the Utopia politics which is based on Utopia. From Farabi’s perspective, politics is synonymous with educating and nurturing the people in Utopia and it works to realize the goals of the ruler of Utopia. The purpose of educating the people of the city has said to be the establishing of a Divine order in the human city. In fact, felicity is held to be achievable only within the framework and the zone of Allah’s law and order. Therefore, the philosopher-prophet, as the ruler of the city, seeks the political administration of the truth and also to administer the Divine commandment and order in the human life. Thus, a new horizon and perspective towards the truth and existence is opened towards the residents of the Utopia and the humanity of mankind is consolidated there. On the other hand, Utopia works like the illumination of the existence; it is the only arena in which existence is realized and manifested.